Changes in aortic root dimensions after ascending aortic repair with concomitant aortic valve replacement - D. S. Panfilov; B. A. Bazarbekova; N. O. Panfilova; V. V. Saushkin; E. L. Sonduev; S. I. Sazonova; B. N. Kozlov (Российский кардиологический журнал, 2023)
The issue of ascending aortic repair with concomitant aortic valve replacement in pa-tients with ascending aortic aneurysm (AscAA) and aortic valve stenosis is still debatable.Aim. To analyze the dimension changes of the preserved aortic root after simultaneous ascending aorta repair and aortic valve replacement.Material and methods. This retrospective study included 102 patients who, from December 2012 to May 2022, underwent simultaneous aortic valve replacement and ascending aorta repair with hemiarch replacement. Patients were divided into 2 following groups based on the aortic valve morphology: group 1 — patients with bicuspid aortic valve (BAV) and AscAA (n=75), group 2 — patients with tricuspid aortic valve (TAV) and AscAA (n=27). Depending on the presence of aortic root dilatation (maximum diameter (d) >40 mm), each of the groups was additionally stratified into 2 more subgroups as follows: patients without aortic root dilatation (d≤40 mm) and patients with its dilatation (d>40 mm). The dynamics of the aortic root diameter was assessed by computed tomography angiography.Results. The mean follow-up period for patients was 36,2±14,6 months. Survival rate in the BAV+AscAA and TAV+AscAA groups was 96% and 100%, respectively (p=0,380). Freedom from aortic root resurgery was 100% in both study groups. In patients with dilated and non-dilated aortic root of the BAV+AscAA group, an increase in aortic root dimension was noted at a rate of 0,65±0,51 mm/year and 0,32±0,27 mm/year, respectively. In patients of the TAV+AscAA group, a regression in dilated and non-dilated aortic root diameter was observed as follows: 0,93±0,48 mm/year and 0,56±0,43 mm/year, respectively.Conclusion. In patients with AscAA in combination with BAV stenosis after a singlestep surgical intervention, a weak negative dynamics of non-dilated and dilated aortic root is observed in the mid-term follow-up period. In patients with AscAA and TAV, there is involutive alterations of the aortic root dimension during 3-year follow-up.